Improving Savings, Health, and Happiness by Making Small Modifications to Your Home - Randall A. Cantrell (EDIS, 2012)
Intended for an academic audience, this 7-page fact sheet introduces readers to the concept of overall home performance and offers suggestions of minor conservation measures, maintenance items, and family operations that could help the family improve the overall home performance. Written by Randall A. Cantrell and published by the UF Department of Family, Youth and Community Sciences, March 2012.